2018
DOI: 10.1002/brb3.1032
|View full text |Cite
|
Sign up to set email alerts
|

Time to steroid treatment in severe acute optic neuritis

Abstract: ObjectivesSteroid treatment can accelerate visual recovery in patients with optic neuritis (ON), but it is unknown whether the timing of the start of treatment influences the outcome. The main purpose of this observational study was to assess the effect of early onset steroid treatment of ON on visual prognosis and retinal morphology.MethodsForty‐nine patients with acute mild/moderate (n = 21) or severe (n = 28) ON, and an equal number of healthy controls were enrolled. Patients with severe ON either received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In people with ON, one study reported improved visual acuity in Thai patients with isolated ON treated within 8 days from onset (79). In another study, early treatment (within 7 days from onset) was associated with better short-term visual outcomes in people with severe acute ON, but long-term visual acuity was not influenced by the timing of treatment (102).…”
Section: Discussionmentioning
confidence: 98%
“…In people with ON, one study reported improved visual acuity in Thai patients with isolated ON treated within 8 days from onset (79). In another study, early treatment (within 7 days from onset) was associated with better short-term visual outcomes in people with severe acute ON, but long-term visual acuity was not influenced by the timing of treatment (102).…”
Section: Discussionmentioning
confidence: 98%
“…Differences between RCI and IVMP may be evident for rarer causes of acute optic neuritis (e.g., aquaporin-4-IgG seropositive neuromyelitis optica spectrum disease or MOGAD) 20 or with more rapid treatment. 21 Although only a single MOGAD optic neuritis patient was enrolled in this study, the low number may have been the result of exclusion criteria (bilateral optic neuritis and severe disc edema or hemorrhage) and the limited availability of commercial MOG-IgG testing. Nevertheless, the data from our trial may be helpful in powering future studies aimed at the identification of therapeutic and neuroprotective agents while using a common signature syndrome for acute ON as a template from which to detect and monitor treatment effects.…”
Section: Discussionmentioning
confidence: 99%